Basic principles of economic policy and public decision in the 21st century - Muñoz, Oscar González; Flores, Milagros Cano (Journal of Social Sciences (COES&RJ-JSS), 2020)
In the midst of the new contributions to economic theory and the new challenges that represent globality as a means of integrating markets through the economic policy of the neoliberal order, versus the consolidation of a neo-institutional system through the defense of the Sovereignty as a nationalism of attention to the conditions of political life, it is necessary to conduct a respectful analysis of the new scenario of international life through current economic theory. The objective of this paper is to carry out an analysis of the known economic policy models through the theoretical contribution of classical economists. It is a theoretical exercise and bases its result on the concretion of the complexity of the economic model currently known.